2022
DOI: 10.2147/dmso.s372192
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Affects Gut Microbiota Structure in db/db Mice by Affecting Insulin, Blood Glucose and Body Weight

Abstract: The purpose of this study was to investigate the regulatory effect of salidroside on the intestinal flora of mice with type 2 diabetes (T2DM) and its protective effect in the body. Patients and Methods:We acclimated 8-week-old mice for 7 days, divided them into 4 groups, and continued dosing for 8 weeks. We recorded weekly blood glucose levels and body weight for each mouse. After the completion of the feeding cycle, the 16S rRNA of the intestinal flora in the mice was sequenced, and the insulin and C-peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Lactobacillus transplantation and administration can improve the symptoms of PCOS, which is conducive to the treatment of PCOS ( Guo et al., 2016 ; Siddiqui et al., 2022 ). Candidatus Arthromitus is involved in body glucose metabolism and is positively correlated with body weight ( Fu et al., 2022 ; Zhao et al., 2022 ). Our study found that T was significantly positively correlated with Enterorhabdus , LH was significantly positively correlated with Lactobacillus , and body weight was significantly positively correlated with Ligilactobacillus , Candidatus Arthromitus .…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus transplantation and administration can improve the symptoms of PCOS, which is conducive to the treatment of PCOS ( Guo et al., 2016 ; Siddiqui et al., 2022 ). Candidatus Arthromitus is involved in body glucose metabolism and is positively correlated with body weight ( Fu et al., 2022 ; Zhao et al., 2022 ). Our study found that T was significantly positively correlated with Enterorhabdus , LH was significantly positively correlated with Lactobacillus , and body weight was significantly positively correlated with Ligilactobacillus , Candidatus Arthromitus .…”
Section: Discussionmentioning
confidence: 99%
“…In both Furan-induced liver injury and high-fat diet (HFD)-induced non-alcoholic steatohepatitis mice, salidroside decreased serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and proinflammatory factor, accompanied by the enhancement of Akkermansia and Roseburia , and decline of Sporobacter , Blautia , Desulfovibrio , Anaerofustis , Olsenella , Bifidobacterium , Vasilyevaea, Lactobacillus and Alloprevotella ( Li et al, 2020 , Yuan et al, 2019 ) . Furthermore, salidroside could reduce the glucose level and protect heart, liver, kidney from diabetes-caused damage, which at least partly mediated by the alteration of gut microbiota, such as the increase of Prdiococcus , Alloprevotella , and decrease of Enterobacter , Lactobacillus , Mycoplasm a, Enterococcus , Candidatus Arthromitus , and Lachnospiraceae UCG-006 ( Shi et al, 2022 , Zhao et al, 2022 ). These results will shed a new light on the future of the targeted and precise modulation of microbiota to treat diabetes mellitus.…”
Section: Gut Microbiota Is a Bridge Linking Pharmacological Effect Of...mentioning
confidence: 99%
“…These products used by the intestinal bacteria, in turn, affect the type and quantity of intestinal microbiota [ 3 ]. Changes in the intestinal microbiota may affect body weight, blood glucose, blood lipids and insulin sensitivity [ 4 ]. Zhou et al [ 5 ] studied the effect of microbiotic changes on insulin resistance and dyslipidemia in mice.…”
Section: Introductionmentioning
confidence: 99%